Hukum Keluarga Islam Dan Hak Warga Negara: Analisis Polemik Perlindungan Hak Anak Luar Nikah - Abdullah Sani, Azhar, Suaib Lubis, (Mediation : Journal of Law, 2023)
In family life, marriage and the birth of children are major events that give rise to complex legal consequences that will remain attached to the human being until death. Indonesia as a rule of law has guaranteed and protected the fulfillment of the constitutional right to marriage for all Indonesian citizens, as stated in Article 28B paragraph (1) of the 1945 Constitution of the Republic of Indonesia which reads: "Everyone has the right to form a family and continue offspring through a legal marriage." A marriage can be said to be valid if it fulfills the provisions in Article 2 of Law Number 1 of 1974 concerning Marriage, namely: (1) "Marriage is valid if it is carried out according to the laws of each religion and belief." (2) "Every marriage is recorded according to the prevailing laws and regulations." It is from this legal marriage that the obligations and rights arising after the marriage can be guaranteed for their fulfillment and protection by the State. One of the common goals to be achieved in married life is to have children. In essence, children are a mandate and a gift from ALLAH SWT, which must always be looked after, because human rights are attached to them which are a gift from ALLAH SWT. The constitutional mandate of Article 28 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia also stipulates that: "Every child has the right to survive, grow and develop and is entitled to protection from violence and discrimination.